IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DAN ANALISIS SWOT DALAM PENGELOLAAN PENDIDIKAN DI SD NO. 2 GULINGAN - Chindytia; Ida Bagus Surya Abadi; Ni Made Sri Dewi Dharmayanti; Ni Putu Diah Agustina Putri; I Ketut Wiranata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the implementation of School-Based Management and to identify the internal and external conditions of the school using a SWOT approach at SD No. 2 Gulingan. This study used a qualitative descriptive method with data collected through interviews and observations. The data were analyzed to describe the strengths, weaknesses, opportunities, and threats faced by the school in managing education. The results showed that the implementation of School-Based Management had been carried out quite well, as indicated by clear planning, proper implementation of learning activities, participatory leadership, and good communication between the school and its stakeholders. However, the school still faced several challenges, particularly related to limited facilities and funding, which were influenced by the relatively small number of students. Through SWOT analysis, the school was found to have opportunities for development through stakeholder support and improvement in learning quality. Therefore, appropriate strategies are needed to utilize existing strengths and opportunities while minimizing weaknesses and threats. The findings of this study are expected to serve as a basis for improving more effective and sustainable school management.